A Paradigm of Faith-Driven Higher Education: Empirical Insights into Universitas Djuanda Kampus Bertauhid’s SDG Implementation Excellence - Siti Pupu Fauziah; Martin Roestamy; Radif Khotamir Rusli; Irman Suherman; Arif Irawan (Universitas Negeri Malang, 2025)
This comprehensive study examines Universitas Djuanda (UNIDA) Kampus Bertauhid as an exemplary model of faith-based higher education that successfully integrates Islamic values with modern academic excellence while contributing significantly to the United Nations Sustainable Development Goals (SDGs). Through a mixed-methods approach combining institutional analysis, stakeholder interviews, and performance assessment, this research reveals how UNIDA's unique Pancadarma framework, extending the traditional Tridarma with Tauhid faith and professionalism, creates a distinctive educational ecosystem. The study demonstrates that UNIDA's integration of pesantren (Islamic boarding school) principles with contemporary higher education not only preserves Islamic character development but also enhances academic performance and social responsibility. Key findings indicate that UNIDA's 21 Tauhid Character Values system produces graduates with superior moral integrity (95% effectiveness), social responsibility (88% impact), and environmental stewardship (87% implementation). The university's commitment to sustainability is evidenced through its comprehensive green campus initiatives, achieving 82% energy efficiency and 35% renewable energy utilization. This research contributes to the growing literature on faith-based education's role in sustainable development by providing empirical evidence of how Islamic educational institutions can serve as catalysts for achieving multiple SDGs while maintaining their religious identity and mission.